(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
As there is only one earth, it is essential to know the relationship in the nature to maintain environmental balance. First challenge is to protect the earth, Green the earth and heal the earth. The depletion in natural resources has lead to unsustainability of the environment. The building sector accounts for 30-40 of the total global energy consumption. Out of which 80 is consumed during the operational stage of building and remaining 20 of during its construction phase. Thus some urgent and hard decisions to be taken to stop the deterioration of the environment.This paper highlights the study of sustainable perspective in which we analyse the buildings in terms of Sustainable Architecture and Design, Site Selection and Planning, Water Conservation, Energy Efficiency, Building Materials and Resources, Indoor Environmental Quality and innovation. The green building study highlights implementation of sustainable practises as per building feasibility with available limited resources to make the building sustainable and to achieve certification.